2013
DOI: 10.1080/19443994.2013.813692
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of biological process using biocoagulation–flocculation pretreatment aid in olive mill wastewater detoxification

Abstract: Olive mill wastewaters (OMWW) are a significant source of potential or existing environmental pollution in the Mediterranean countries. Treatment and reuse of OMWW present significant challenges, both due to the nature of olive oil production (seasonal and concentration in a small scale) and due to the characteristics of the wastewater (high chemical oxygen demand (COD) and high phenolic content). In the present work, experiments of different pretreatment methods were undertaken and compared in order to select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(45 reference statements)
1
2
0
Order By: Relevance
“…The phenolic fraction after its extraction from OMWW with an ethyl acetate solvent was analyzed by HPLC chromatograph. It was found that Hydroxytyrosol and Tyrosol are the most predominant polyphenols with more than 95%, the same result was found by several authors [41]. The following polyphenols were also identified: Syringic acid, gallic acid, Catechol and Caffeic acid (Fig.…”
Section: B Characterization Of Omwwsupporting
confidence: 83%
“…The phenolic fraction after its extraction from OMWW with an ethyl acetate solvent was analyzed by HPLC chromatograph. It was found that Hydroxytyrosol and Tyrosol are the most predominant polyphenols with more than 95%, the same result was found by several authors [41]. The following polyphenols were also identified: Syringic acid, gallic acid, Catechol and Caffeic acid (Fig.…”
Section: B Characterization Of Omwwsupporting
confidence: 83%
“…Colic et al (2007) showed that flotation is used to remove as much solids, oils and fats as possible. In general, removal of turbidity in OMW was widely done by electrocoagulation, with a rate between 75% and 82% (Khani et al, 2019; Neffa et al, 2014). These high removal rates can be explained by the good efficiency of the electrocoagulation treatment in a short duration (45–90 min), and also the fact that the raw OMW used present low total suspended solids between 3.4 and 6.4 g/L.…”
Section: Resultsmentioning
confidence: 99%
“…The vegetation water (OMWW) and the pomace (OMSR) have an acidic pH, high values of chemical demand (COD) and biochemistry (BOD 5 ) of oxygen, low nitrogen content, and the presence of lipids and a phenolic fraction [9,10]. The high organic load (45-220 g/L of COD) represents a significant energy potential and would make the olive wastewater one of the most suitable agro-industrial wastes for anaerobic digestion [11,12].…”
Section: Introductionmentioning
confidence: 99%